Global Synergy: the importance of language and oral presentations in uniting science, research, and community service - Vijayarajoo, Angeline Ranjethamoney; Saleh, Noor Shahariah; Azmi Salmi, Sharina; Adnan, Afni Anida (2025)
This paper attempts to unlock keywords used in the theme of this Colloquium while positioning Language and Oral Presentations as key for Global Synergy. This paper brings together related works showing the importance of Language through effective oral presentations. This is the basis for Global Synergy of any kind to be achieved. Science and Research can only be made available to Communities through the medium of language. English is the global language, and this study focusses on oral presentations. Communication through Language and the subskill of Oral presentations is the vehicle for knowledge transfer in any field, as well as reaching out to Communities. While much emphasis is given to science and the field of Research, less is said of the Global Language, English, which is mandatory. How can Science and research findings reach communities if not through the medium of the global language? This study was conducted with undergraduates in a local public university and confirms previous findings. These findings reveal their awareness of the importance of effective oral presentation, while highlighting their lack of confidence and nervousness during such activities. This is an area of great concern to achieve effective oral presentations in English for Global Synergy among all communities. This study also provides suggestions on how these challenges can be addressed.